213k views
16 votes
Solve for x

Enter the solutions from least to greatest.
(3x – 6)(-x + 3) = 0

lesser x =
greater x =

User Frostless
by
6.3k points

1 Answer

9 votes
The lesser x is 2 and the greater x is 3. The x values can be determined by setting each set of numbers in parenthesis equal to 0, so 3x-6=0 and -x+3=0. To solve, take the first set, 3x-6=0 and divide by the greatest common factor, 3, leaving you with x-2=0. Add 2 to each side so that x=2. On the other side, take -x+3=0 and subtract three from each side. Take your new equation -x=-3 and multiply by -1 so that x=3. Therefore x=3 and x=2.
User Enezhadian
by
5.8k points